Application of a layered rubber composite to reduce dynamic effects on steel structures - Major, Maciej; Major, Izabela; Różycka, Judyta (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The purpose of paper is to analyze a layered rubber composite aimed at significant reduction in dynamic effects on steel structures. In the first part of the paper there is presented an analytical analysis of transverse and longitudinal acoustic wave propagating in a layered rubber composite made of a material with elastic potential Blatz - Ko. The second part discusses a numerical example showing the behavior of the surface discontinuities propagating in this layered composite, showing the distribution of stresses for the assumed potential and constant material from the first part of the paper. In the paper seeking possibilities of application of the composite inter alia in order to reduce the dynamic effects generated in the process of emptying silos from granular materials which can cause their failures and for the group of silos can lead to the creation and propagation of dynamic oscillations in the subsoil which threaten building located nearby. Issue adopted at work and the obtained results provide the basis for the further numerical study expanding the results.